THE IMPORTANCE OF INNOVATION IN THE PERFORMANCE OF IPO PROCESSES THAT OCCURRED IN BRAZIL DURING THE LAST DECADE - Sampaio, Murilo (Future Studies Research Journal: Trends and Strategies, 2012)
Innovation is a challenge sought by all economically developed societies. National systems articulate public and private resources so as to shape a more innovative society, capable of ideating and promoting processes, products and services with increasing levels of differentiation before those existing. The search for innovation and the creation of competitive advantages is even greater in the corporate environment, a microeconomic locus where innovation can be measured by efforts and results obtained. Likewise, the number of companies that seek to open themselves to the capital market with views to accumulating resources so as to sustain their strategic growth plans, increases. During the last decade, 245 companies opened their capital in Brazil but only 40% of these went to São Paulo´s Stock Exchange Market (Bovespa) negotiate their shares. Upon making its Initial Public Offering (IPO) the company has to expose to the stock exchange market its true situation in several areas which are ruled by the Securities and Exchange Commission (CVM). They produce extensive documentation in the form of a robust prospect that is made available to any potential investor. The prospect is known at the capital market as the source that portrays the largest amount of information concerning the company that announced their IPO. It is a legal document but, at the same time, one that in highlight contains, all the attributes and differentials that the company expects the market to evaluate. Thus, by means of secondary sources, all ground on the prospects of IPOs that took place, research was conducted to acknowledge the level of innovation each company presented at the time of their IPO and, at the same time, to measure the performance of the value of stocks that the respective IPO obtained. Subsequently a set of structured qualitative interviews posing to evaluate the results of the quantitative research, was conducted. The quantitative analysis of data collected did not reveal significance between the innovation variable and the performance stocks obtained at the time of market launch. This same conclusion was ratified during the interviews conducted with the economic agents that operated most of the IPOs which occurred in Brazil. Therefore, despite the relevance of the theme innovation for the qualitative development of an economy (and, in special, for one of the largest economies in the world), results indicate the absence of correlation between innovation and IPO performance. They further offer possible approaches that can extend the study concerning the theme (including other variables, considered of greater relevance and which influence IPO performance), rendering further precision to interpretations and conclusions presented herein.